4y + mx - 4x - my
=4(y-x) -m(y-x)
=(4-m)(y-x)
2007-11-22 10:44:47
·
answer #1
·
answered by A 150 Days Of Flood 4
·
2⤊
0⤋
Did you follow what 150 days of flood was doing? He gathered the terms that had common factors, 4y and 4x and since a subtraction was involved it became 4(y-x). Likewise with mx and -my. have fun!
2007-11-22 10:54:16
·
answer #2
·
answered by St N 7
·
0⤊
0⤋
4y + mx - 4x - my
4y - my + mx - my (rearranging the equation)
y(4 - m) + m (x - y) (grouping the common terms)
2007-11-22 11:00:58
·
answer #3
·
answered by nike s 2
·
0⤊
0⤋
4(y-x) +m(x-y)
to factor something..so have to have something in common..
so 4 is common in two..so i know I needed 4(y-x) because when i multiply this out I will have 4y-4x
m is the common factor in the other 2, and when i multiply
m(x-y) I end up with mx-my
I know my answer is right, but i have to say...the first guy probably simplified the expression even better than I did
2007-11-22 10:49:59
·
answer #4
·
answered by Anonymous
·
1⤊
0⤋
4y + mx - 4x - my
First write it in common form
=4y-4x+mx-my
take common 4 and 'm' are common
=4(y-x) -m(y-x)
Now write the first term and second term
=(y-x)(4-m) This is your answer
2007-11-22 11:20:45
·
answer #5
·
answered by C63AMG 5
·
0⤊
0⤋
4y + mx - 4x - my
= 4y -my + mx - 4x
= y(4-m) + x(m-4)
= -y(-4+m) + x(m-4)
= (m-4) (x-y)
2007-11-22 10:52:00
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
Note that there are 2 4's, 2 m's, 2 x's and 2 y's. looks like a cross product (4-m) (y-x).
Note that the - terms are chosen to yield negative terms where required.
2007-11-22 10:50:05
·
answer #7
·
answered by Computer Guy 7
·
1⤊
0⤋
4y+mx-4x-my
4y-4x+mx-my
4(y-x)+m(x-y)
2007-11-22 11:05:12
·
answer #8
·
answered by Varsh p 2
·
0⤊
0⤋
4y+mx-4x-my=4y-4x+mx-my=
=4(y-x)-m(y-x)=(y-x)(4-m)
second method
4y+mx-4x-my=4y-my-4x+mx=
=y(4-m)-x(4-m)=(4-m)(y-x)
2007-11-22 10:59:53
·
answer #9
·
answered by inadida 1
·
0⤊
0⤋
first:y=7 x=4 m=5
second: answer is 2. or y(-4)
2007-11-22 10:47:54
·
answer #10
·
answered by Anonymous
·
0⤊
2⤋